2017
DOI: 10.1136/bmjopen-2017-016512
|View full text |Cite
|
Sign up to set email alerts
|

The Taking Charge After Stroke (TaCAS) study protocol: a multicentre, investigator-blinded, randomised controlled trial comparing the effect of a single Take Charge session, two Take Charge sessions and control intervention on health-related quality of life 12 months after stroke for non-Māori, non-Pacific adult New Zealanders discharged to community living

Abstract: IntroductionStroke is one of the leading causes of disability worldwide. Recent data support the possibility that person-centred, self-management interventions can reduce dependence after stroke. However, there is limited information on the generalisability and optimum dose of these interventions.MethodsThe Taking Charge After Stroke (TaCAS) study is a multicentre, investigator-blinded, randomised controlled trial recruiting 400 participants following acute stroke from seven hospitals in New Zealand. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The design, interventions, and main measures of the Taking Charge after Stroke trial have been reported previously. 1,21 This was a prospective, randomised, open trial of two active and one control intervention with blinded endpoint assessment in seven centres in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…The design, interventions, and main measures of the Taking Charge after Stroke trial have been reported previously. 1,21 This was a prospective, randomised, open trial of two active and one control intervention with blinded endpoint assessment in seven centres in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were enrolled between October 2015 and August 2017. The full study protocol and results of the Taking Charge after Stroke trial, containing a full description of the study methods, are published elsewhere [4,6]. In brief, this was a prospective open-label randomised controlled trial comparing the Take Charge intervention to a control intervention with masked endpoint assessment.…”
Section: Methodsmentioning
confidence: 99%
“…The full study protocol and results of the Taking Charge after Stroke trial, containing a full description of the study methods, are published elsewhere. 4,6…”
Section: Methodsmentioning
confidence: 99%
“…Recruitment to the target of 400 participants was achieved close to schedule within 22 months. The trial was completed keeping to the original protocol which was published halfway through the trial (Fu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial part of this chapter has been previously published in BMJ Open as the TaCAS study protocol (Fu, Weatherall, & McNaughton, 2017). Acknowledgements are made to the other authors, Dr Harry McNaughton and Prof. Mark Weatherall, who provided feedback on the original manuscript.…”
Section: Methodsmentioning
confidence: 99%